Functional outcome in low-ASPECTS (0–5) acute ischemic stroke treated with mechanical thrombectomy: impact of laterality explored in a single-center study - Dumas, Victor; Martin, Killian; Giraud, Clément; Prigent, Julia; Bloch, William; Soualmi, Karim; Herpe, Guillaume; Boucebci, Samy; Neau, Jean Philippe; Guillevin, Rémy; Velasco, Stéphane (Frontiers in Neurology, 2023)
Background: There is no consensus regarding the influence of infarct laterality in patients with acute ischemic stroke due to anterior large vessel occlusion (AIS-LVO) treated with mechanical thrombectomy (MT), particularly in low ASPECT (0-5) patients who were largely excluded from the first MT studies. We aimed to evaluate the role of infarct laterality on the clinical outcome in low ASPECT AIS patients treated with MT. Material and methods: We retrospectively analyzed our institutional stroke database in our Thrombectomy-Capable Stroke Center (TCSC) including patient characteristics, procedural variables, and outcomes between January 2015 and January 2022. Patients with acute intracranial ICA and/or proximal MCA occlusions with ASPECT ≤ 5 either on CT or MRI were included and separated into 2 groups according to the location of ischemia. A good clinical outcome at 90 days (modified Rankin Scale (mRS) score of 0-3) was the primary end point. Results: Between January 2015 and November 2021, 817 MT were performed, of which 82 were low-ASPECT (10.0%): 41 left sided and 41 right sided strokes. The rates of good clinical outcome were 30,8% (12/41) for left sided group, and 43,6% (17/41) for right-sided group; pvalue 0.349. There was no significant difference in the mortality rate: respectively 39.0% (16/41) in the right stroke group and 36.6% (15/41) in the left one. Conclusion: Clinical outcome was not significantly influenced by stroke laterality. The results of this single-center retrospective study suggest either a lack of strength or equal value in performing mechanical thrombectomy regardless of stroke laterality.